Моделі та методи автоматизованого проектування технологічних процесів виготовлення мікроелектромеханічних акселерометрів - Бортнікова, В. О. (ХНУРЕ, 2019)
Дисертаційна робота присвячена вирішенню науково-технічної задачі підвищення ефективності автоматизованого проектування технологічних процесів (ТП) виготовлення мікроелектромеханічних (МЕМС) акселерометрів шляхом розробки математичних моделей, методів і програмного забезпечення. Вперше розроблено математичну модель визначення МЕМС акселерометра-аналога, для якої формалізовано критерії часу і вартості виготовлення, маси та площі МЕМС акселерометра та враховано функціонально-конструктивні обмеження, що дозволяє визначити найкращій варіант МЕМС акселерометра-аналога для здійснення вибору типового технологічного процесу. Удосконалено модель структурно-параметричного синтезу технологічного процесу виготовлення МЕМС акселерометрів, яка, на відміну від відомих, шляхом вибору типового технологічного процесу, операцій і обладнання, дозволяє отримати структуру технологічного процесу і у випадку необхідності обрати більш ефективне технологічне обладнання. На основі моделі структурно-параметричного синтезу ТП виготовлення МЕМС акселерометрів розроблено імітаційну модель. На основі цих моделей вперше розроблено узагальнений метод автоматизованого проектування технологічних процесів виготовлення МЕМС акселерометрів, який базується на двох часткових методах: вибору типових ТП і пошуку аналогів окремих елементів технологічного процесу, що дозволяє отримати ефективній технологічний процес за рахунок зниження вартості та часу виготовлення. Проведено удосконалення методу вибору типових ТП виготовлення МЕМС акселерометрів. Розроблені й удосконалені математичні моделі та методи дозволили отримати математичне, інформаційне та програмне забезпечення систем автоматизованого проектування, яке реалізовано в програмному модулі «AcCAM». An important role in Industry 4.0 technology is played by modern technical means of automation (sensors, actuators, regulators, etc.), which must provide required level of accuracy, operation speed parameters, small weight-size characteristics, high functionality, low power consumption and cost. According to this, wide-ranging applications have been made by sensors using microelectromechanical systems (MEMS) technology. Today, MEMS sensors are represented by a large variety of types, but the most intensively and dynamically developing are MEMS accelerometers, which are widely applied in different industries. The development of new MEMS accelerometers and their production technology is associated with a complex scientific and technical task of providing geometric and functional parameters that affect manufacturing technology. The technology of manufacturing MEMS accelerometers combines a variety of modern technological techniques of microelectronics. Their totality forms a set of variants of technological process and their sequences, which cannot be implemented without the use of Aided design systems (CADx).The model of structural-parametric synthesis of the technological process of MEMS accelerometers production is improved by choosing the best variant of a typical technological process, which allows to obtain the preliminary technological process structure at the different level stages, operations and routes. The synthesis of the technological process structure is by the selection of typical technological process, operations and equipment. The choice of a typical technological process is based on the criterion of cost, and the choice of operations according to the criteria of cost and execution time. In case of need, more efficient technological equipment can be selected based on the criteria of productivity, energy consumption, cost and service life. Based on the model of structural-parametric synthesis of technological process for the MEMS accelerometer production the simulation model was developed. The obtained model allows to evaluate the adequacy of the obtained technological process structure and to develop options for improving the efficiency of technological process for each decision. For the first time a generalized method of aided design of technological process was developed, based on two particular methods: the choice of typical technological process and the search for analogues of technological process individual elements. Such an integrated use of two methods can increase the efficiency of design work at the expense of cost and time. The method of selecting typical technological process for MEMS accelerometers production by cost and time figures and based on hierarchical clustering method and data mining methods has been improved, which allowed increasing the efficiency of making project decisions. The developed and improved mathematical models and methods allowed obtaining the aided design systems mathematical, informational support and software, which were implemented in the program module «AcCAM» to solve the problem of technological process automated design for the MEMS accelerometers production.
Keywords: мікроелектромеханічні системи (МЕМС); акселерометр; технологічний процес; автоматизація проектування; microelectromechanical systems (MEMS); accelerometer; technological process; automated design